Aggregation Induced Emission Enhancement (AIEE) of Naphthalene‐ Appended Organic Moiety: An Al3+ Ion Selective Turn‐On Fluorescent Probe. Issue 1 (2nd January 2020) - Mondal, Asit; Ahmmed, Ejaj; Chakraborty, Sujaya; Sarkar, Arnab; Lohar, Somenath; Chattopadhyay, Pabitra
Abstract: An example of an aggregation‐induced emission enhancement (AIEE)‐active new naphthalene appended Schiff base (H2 L ) as an Al 3+ ion selective fluorescent sensor has been successfully designed and synthesized. H2 L showed turn‐on fluorescence at high concentration in DMF only, and at low concentration in DMF‐H2 O mixtures having high water content (more than 20%). But at very low concentration of H2 L and in DMF/H2 O solutions with low water fraction (fw ≤ 20%), the fluorescence was turned ON in presence of Al 3+ ions, which helps to detect Al 3+ ions as low as 4.9×10 −7 M with high selectivity in an DMF solution without any interference of other competitive metal ions. The fluorescence of H2 L in different conditions and in solid state due to AIE effect has been established with the help of detailed spectroscopic studies, dynamic light scattering (DLS), scanning electron microscope (SEM), life time using time‐resolved photoluminescence and optical fluorescence microscope. The experimentally observed H‐type aggregation nature of the probe H2 L has also been supported by the theoretical (DFT studies and TDDFT) studies. This probe (H2 L ) has also been employed for on‐site Al 3+ ions detection in solid state. Abstract : A new spectroscopically characterised naphthalene appended Schiff base (H2 L) senses selectively Al 3+ ions as low as 4.9 x 10 −7 M based on H‐type aggregation‐induced emission enhancement (AIEE) with almost no interference of competitive ions. The AIE effect has been established with the help of detailed theoretical and experimental studies. This probe (H2 L) is also efficient candidate of detecting the distribution of Al 3+ ions in paper strips test and solid state under fluorescence microscope.